Counselling at School: A Comparison of the Work Characteristics of School Counselling Professionals in Four Different Countries - Pociūtė, Birutė; Bulotaitė, Laima; Lazauskaitė-Zabielskė, Jurgita (Acta Paedagogica Vilnensia, 2019)
The technological revolution, the ever-changing economic and political conditions, and the resulting changes in life and work environments impede career planning for young people and pose challenges for career counselors in career orientation. Nowadays, career counselors have to not only assist students in planning and implementing individual, social, academic, and career goals, but they must also help the school community to ensure the effective functioning of schools in general. There is a lack of studies focusing on various aspects of career counselors’ professional activities, with the existing studies providing inconsistent or even contradictory results. Another problem lies in the huge gap between the theoretical, methodological, and methodical career counseling models and real counseling experience. Therefore, this study was conducted with the aim of analyzing and comparing the characteristics of career counselors’ professional activities in Lithuania, Italy, Greece, and Ireland. The study was part of the project “Strategies to Utilise and Cultivate Positive Characteristics & Employability Skills in Schools” (SUCCESS, 2017-12-LT01-KA201-035247).In total, 289 school career counselors from Lithuania, Italy, Ireland, and Greece were surveyed. Most of the participants (90 percent) were female, and their age varied between 25 and 60 years. In all countries, the professional experience of career counseling varied between 1 and 10 years.The results of this study revealed that across different countries, career professionals with different educational backgrounds perform career counseling. In Lithuania, career counselors are mainly psychologists, in Italy – teachers, in Ireland – consultants, and in Greece – teachers, psychologists, and consultants that carry out career counselling. The results have also shown that in all these countries career counselors perform various career counseling activities: career information, career assessment, career education, and career consulting using (non)psychological methods, although the frequency of these activities and the subjective readiness for them is different across countries. The counselors in all countries are satisfied with their jobs. Despite the existing differences in needs for professional development, all counselors expressed a higher-than-average need to develop their career counseling competencies.
Keywords: school counseling professionals; counselor roles; job satisfaction